2017
DOI: 10.1111/anu.12555
|View full text |Cite
|
Sign up to set email alerts
|

Dietary riboflavin requirement of fingerlingChanna punctatus(Bloch) based on growth, conversion efficiencies, protein retention, liver riboflavin storage, RNA/DNA ratio and carcass composition

Abstract: A 16‐week experiment was conducted to determine the dietary riboflavin requirement of the fingerling Channa punctatus (6.7 ± 0.85 cm; 4.75 ± 0.72 g) by a feeding casein–gelatin‐based (450 g/kg crude protein; 18.39 kJ/g gross energy) purified diet containing graded levels of riboflavin (0, 2, 4, 6, 8, 10 and 12 mg/kg diet) to triplicate groups of fish near to satiation at 09:30 and 16:30 hr. Absolute weight gain (AWG), protein efficiency ratio (PER), specific growth rate (SGR, % per day), protein retention effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…As this fish is a slow growing species (Jindal et al., ; Nassr et al., ), lower values of feed and protein retention efficiency obtained in this study were also reported by Jindal et al. (), Zehra and Khan () and Nassr et al. () in the same fish species.…”
Section: Discussionsupporting
confidence: 83%
“…As this fish is a slow growing species (Jindal et al., ; Nassr et al., ), lower values of feed and protein retention efficiency obtained in this study were also reported by Jindal et al. (), Zehra and Khan () and Nassr et al. () in the same fish species.…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, diets deficient or excess in dietary copper showed reduced Hb and RBC count. Lower values of Hct, Hb and RBC counts have been acknowledged as the indications of anaemia in fish (Lin, Lin, & Shiau, 2012;Zehra & Khan, 2018). Decreased immunity, negative effect on the heartbeat, disturbance of respiratory system and other behavioural changes develop as a result of excess dietary copper (Ajani & Akpoilih, 2010;Das & Gupta, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…When ROS generation rate is higher than their removal rate, it results in increased oxidative stress causing damaging effects such as lipid peroxidation, DNA damage and protein oxidation. To combat the effect of ROS attack, fish have developed enzymatic antioxidant defence system consisting of SOD, CAT, GPx, glutathione reductase and non‐enzymatic glutathione (Zehra & Khan, ). Antioxidant enzymes act in an intricate and coordinated manner in order to ensure defence against oxidative stress (Hermes‐Lima, ; Zehra & Khan, ).…”
Section: Discussionmentioning
confidence: 99%
“…RNA is directly involved in protein synthesis, and therefore, increases in RNA content are observed during periods of rapid growth, whereas DNA content is usually stable (Bulow, ) making the RNA/DNA ratio an indicator of protein synthesis capacity per cell. The RNA/DNA ratio is thus a frequently measured indicator of growth rate in several studies (NRC, , Zehra & Khan, , , 2017b). In this study, RNA/DNA ratio was found to improve with the increase in dietary thiamin concentrations up to 2.5 mg thiamin kg −1 .…”
Section: Discussionmentioning
confidence: 99%
“…The liver was removed from another three fish of each replicate tank of treatments and pooled, and five subsamples were taken for the assay of superoxide dismutase (SOD) and catalase (CAT). SOD and CAT activities were estimated as per the methods adopted by Zehra and Khan (). Liver SOD activity is expressed in unit per milligram of protein (U/mg protein).…”
Section: Methodsmentioning
confidence: 99%